Jepun di Borneo utara : migrasi dan kegiatan ekonomi 1884-1941 - Md. Shaffie Abd Rahim (Kota Kinabalu, Sabah : Penerbit UMS, 2007)
Migration and economic conditions of the Japanese in North Borneo from 1884 to 1941
Keywords: Japanese -- Sabah -- History; Japanese -- Sabah -- Economic conditions